Performance Analysis of AODV & MAODV Protocol in Mobile ADHOC Networks - Singh, Gurjeet; Dhir, Vijay (International Journal of Computer Sciences and Engineering, 2018)
A Mobile Adhoc Network made up of mobile nodes which are wireless. Mobile Adhoc Network is self organized and self configurable. In MANET mobile nodes move randomly. Like a router, the mobile nodes in MANET can forward and receive packets. Routing is a critical issue in MANET. A recent trend in adhoc network routing is the reactive on-demand philosophy where routes are established only when they are required. Most of the protocols in on -demand category are not associating with proper security features. The adhoc environment can be accessed by both legitimate network users and attackers. It has been monitored that different protocols need different security strategies. This paper will discuss the performance analysis of AODV & MAODV protocol in Mobile Adhoc Network.